2005
DOI: 10.1097/01.wnn.0000151859.19031.e8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Leukoaraiosis to Cognitive Decline and Cognitive Aging

Abstract: Objective: Leukoaraiosis (LA) is a common finding on MRI scans of the elderly. However, its exact relationship to cognitive decline and dementia is in dispute. Because LA involves the paracallosal white matter, we sought to determine if LA, uncomplicated by ischemic lesions or complaints of cognitive impairment, is associated with cognitive loss or difficulties with interhemispheric integration of behavioral functions.Methods: Two hundred fifty-seven MRI scans with deep white matter changes were screened. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 55 publications
(77 reference statements)
0
19
0
1
Order By: Relevance
“…3,4 The possible correlation of LA with cognitive decline or motor deficit has been investigated using visual or computerized methods to assess the LA extent. [5][6][7][8][9][10][11][12][13][14][15][16] Diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) are MR techniques sensitive to changes in the diffusion properties of water protons in terms of apparent diffusion coefficient (ADC), mean diffusivity (MD), or fractional anisotropy (FA). Previous studies using region of interest measurements have demonstrated that MD and FA in patients with LA are altered not only in the areas exhibiting signal intensity changes in T2-weighted images but also in the normal-appearing white matter.…”
mentioning
confidence: 99%
“…3,4 The possible correlation of LA with cognitive decline or motor deficit has been investigated using visual or computerized methods to assess the LA extent. [5][6][7][8][9][10][11][12][13][14][15][16] Diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) are MR techniques sensitive to changes in the diffusion properties of water protons in terms of apparent diffusion coefficient (ADC), mean diffusivity (MD), or fractional anisotropy (FA). Previous studies using region of interest measurements have demonstrated that MD and FA in patients with LA are altered not only in the areas exhibiting signal intensity changes in T2-weighted images but also in the normal-appearing white matter.…”
mentioning
confidence: 99%
“…factors. The lack of correlation is not completely surprising since the clinical impact of the severity of white matter lesions on cognition is also under discussion [31,32] . However, we did fi nd a signifi cant correlation between the N 2 latency and the total neuropsychological score, while this was not the case with P 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of LA is closely related to circulation disorder of white matter adjacent to the lateral ventricle wall, cerebrospinal fluid circulation disorders and cerebral edema; temporarily no evidence showed that LA is directly related to atherosclerosis. But LA may result in subcortical infarction and cerebral hemorrhage, and is an independent predictor of stroke [14] ; the more severe white matter lesions, the lower regional cerebral blood flow, the worse cerebral autoregulation [15] , reflecting higher levels of ICAM-1, a blood marker of endothelial damage [16] . When LA with cerebral infarction, cerebral hemorrhage, cerebral micro hemorrhage is the mixed group of this study, representative of severe white matter lesions; So mixed group had more obvious correlation with cerebral arteriosclerosis, but it was not necessary that mild LA was related to cerebral arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%